Formulation of Semi Solid Lip Dying From Extract Areca Seeds (Areca Catechu L.) With Several Concentrations - latirah latirah; Lisawati Tanzil; Desiant Hartanti; Priyanto Dwi Nugroho (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Areca nut (Areca catechu L.) is a natural dye as a substitute for synthetic dyes which are less safe for skin health. This study aims to make a semi-solid form of lip color cosmetic preparations with several concentrations. Extracts was made by soaking the powder using 96% ethanol.The results of this reseach is that the lip color has a vanilla smell, soft and homogeneous texture, visually brown color, pH 6.00 to 6.50. Melting point between 41 – 440C Color release test or smear test for a 40% concentration formula shows a good and homogeneous color. Chemical test results using a chromameter formula 20% 0HUE 34.87 (red), 30% 23.10 (red) and 40% 15.03 (purple red)